Why do costs act as a barrier in maternity care for some, but not all women? A qualitative study in rural Nepal. Issue 8 (5th August 2014) - Simkhada, Bibha; R. van Teijlingen, Edwin; Porter, Maureen; Simkhada, Padam; P. Wasti, Sarada
Abstract : Purpose: – The purpose of this paper is to analyse cost as a barrier to the uptake of antenatal care (ANC) in rural Nepal amidst a variety of barriers and facilitators. Design/methodology/approach: – A qualitative study with face-to-face interviews were conducted with 50 ANC users and non-users participants. The setting is rural Nepal, some 20 kilometres outside the capital Kathmandu. Interviews were audiotaped, transcribed and translated into English and results were presented thematically. Findings: – Cost was sometimes a barrier to seeking ANC for poor rural women. It included transport costs, opportunity costs of not being able to work in the household and service-related costs (such as blood or urine tests). The effect of cost as a barrier varied between women of different socio-economic status. Cost was a barrier to accessing ANC partly due to the women's lack of control over household resources. Social implications: – It is important to consider cost in the wider socio-economic context of rural people's lives as financial costs alone do not explain the level of uptake of ANC. Originality/value: – This study provides an original insight of women's experiences on financial issues relating to the use of ANC services in Nepal. Another important aspect of this study was approached with the multiple respondents (i.e. women, their husbands and their mothers-in-law) regarding the use of ANC and financial impact in the use of services. The findings of this study have important implications in health policy formation by providing clear picture of women's financial situation in access to ANC.